VIDEO PEMBELAJARAN TARI JEPIN KEMBANG MANGGAR UNTUK SISWA SMA DI KOTA PONTIANAK KALIMANTAN BARAT - Satrianingsih, Aline Rizky Oktaviari; Putri Aditya, Mega Cantik; Oktariani, Dwi; Patriantoro, Patriantoro (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2023)
The Jepin Kembang Manggar Dance learning video is an alternative traditional dance learning media that is based on Malay culture in West Kalimantan. This learning media was developed using the Research and Development research method. The Jepin Kembang Manggar dance originates from Batu Layang, West Kalimantan, which was created with the aim of remembering that life must have a sense of togetherness, mutual cooperation and joy, because in society you cannot live without other people. The material for this dance is divided into 7 learning videos consisting of movement videos for ragam 1, ragam 2, ragam 3, ragam 4, ragam 5, ragam 6, a video of the posture of holding a manggar, and a performance video of the Jepin Kembang Manggar Dance. This learning video was developed to meet the needs of high school students in the city of Pontianak in studying traditional Malay dance as a medium for instilling and stimulating noble character values. Apart from that, through this video students of senior high schools can improve their skills independently or in groups.